SUSTAINABLE AWARENESS, INFORMATION TECHNOLOGY QUALITY, AND GOVERNMENT SUPPORT ON SUSTAINABLE MEDICAL TOURISM IN ABU DHABI - Faisal Saif Salem Saif Almazrouei; Salmi Mohd Isa (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study aims to assess the impact of sustainable awareness (social, economic, and environmental) on the sustainable medical tourism, that indirect path is explained by information technological quality, and government support (incentives) of Abu Dhabi makes it more strengthen the relationship underpinned by Social Exchange Theory. Extent of previous literature has been highlighted the dearth of research in the context of tourism, but this study concentrated on the medical tourism in the context of Abu Dhabi. To sustain the objective, the data will be collected from the medical tourists from other countries who intend to or have already received medical assistance from Abu Dhabi’s health sector and will follow the purposive sampling technique for data collection. For fruitful insights, the data will be analyzed through SPSS, and Smart PLS. The findings of the current study postulate that sustainable awareness (social, economic, and environmental) has a significant contribution towards the sustainable medical tourism through information technological quality, additionally, the path is become strengthen due to the government support (incentives) of Abu Dhabi. Moreover, the current study recommends several suggestions to the policymakers and practitioners that create awareness of sustainable (social, economic, and environmental) to promote sustainable medical tourism, additionally, the Abu Dhabi’s government are suggested that to make the policies to encourage the tourism.